2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--32251
|View full text |Cite
|
Sign up to set email alerts
|

Board 139: Engineering Leadership Identity: A Qualitative Approach to Understand the Intersection of Engineering and Leadership Identities

Abstract: pursuing a B.S. in Industrial and Management Systems Engineering and a B.A. in Honor's Liberal Studies. Romy is a member of IISE, Alpha Pi Mu, and the Montana State Women in Engineering Advisory Board. Her previous professional experience includes an internship with The Boeing Company and undergraduate research work with the Space Science and Engineering Lab at Montana State.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The Montana State framework combines the LID model discussed above with a community of practice model (Lave & Wenger, 1991). Early results suggest that engineering students may experience conflict between a leadership identity and an engineer identity (Beigel et al, 2019), concurrent with the working engineers' attitudes reported in the Toronto studies.…”
Section: Leadership Identities Within the Engineering Contextmentioning
confidence: 72%
“…The Montana State framework combines the LID model discussed above with a community of practice model (Lave & Wenger, 1991). Early results suggest that engineering students may experience conflict between a leadership identity and an engineer identity (Beigel et al, 2019), concurrent with the working engineers' attitudes reported in the Toronto studies.…”
Section: Leadership Identities Within the Engineering Contextmentioning
confidence: 72%
“…Their proposed model combines engineering identity (technical skill development, self/other recognition as engineer) with leadership identity (leadership skill development, leadership beyond position) and includes acknowledging engineering as a leadership profession. Beigel et al (2019) follow up this work qualitatively, holding focus groups of engineering students who participated in a research program. Students reported the importance of their gender identities, internship experiences, specific courses (such as design), and interaction with mentors as impacting their engineering and leadership identities (Beigel et al, 2019).…”
Section: Who Am I?mentioning
confidence: 99%
“…Beigel et al. (2019) follow up this work qualitatively, holding focus groups of engineering students who participated in a research program. Students reported the importance of their gender identities, internship experiences, specific courses (such as design), and interaction with mentors as impacting their engineering and leadership identities (Beigel et al., 2019).…”
Section: Engineering Leadership Education Frameworkmentioning
confidence: 99%